Effect of polyolefin macro fibers and handmade GFRP anchorage system on improving the bonding behavior of GFRP bars embedded in self-compacting lightweight concrete. (30th August 2020) - Doostmohamadi, Alireza; Karamloo, Mohammad; Afzali-Naniz, Oveys
Highlights: Effect of polyolefin macro fibers on bond behavior of GFRP bars has been assessed. Efficacy of different anchorage systems on bond behavior of GFRP bar was evaluated. Fracking mode of specimens were changed were the fibers were added to the mix. Different codes showed far too conservative results than experiments. Abstract: In the present paper, effect of polyolefin based macro fibers as well as handmade GFRP anchorage system on the improvement of the bond between GFRP bars and self-compacting lightweight concrete, SCLC, has been assessed. To do so, 60 direct pull out tests have been carried out, in which parameters were the compressive strength of concrete (21 MPa, 30 MPa, 36 MPa, and 40 MPa), length, and diameter of anchorage system. Besides, two fiber volume fractions of 0.3% and 0.5% by concrete volume and four types of handmade anchorage systems have been considered. All tests were carried out in displacement control condition by means of a closed loop servo-electro controlled universal testing machine and the loading rate was set to 1.2 mm/min. The slip of bar at free ends, was measured by means of linear variable differential transformers. Test results indicated that the fibers eliminated the concrete splitting. Moreover, not only the fiber contents enhanced the maximum developed stress of the GFRP bars, but also the combination of 0.5% fiber volume fraction and DA2 anchorage system showed the best performance among all specimens.